MINUMAN OLAHRAGA DAN PENINGKATAN PERFORMA ATLET - NOORDIA, ANNA (Arena, 2013)
Body fluid losses during exercise can be very high, and if the fluid is not replaced quickly, dehydration will follow. This will have an adverse effect on athlete’s physical performance and health. Exercise will be much harder and suffer fatigue will be sooner. It is important to drink fluids to avoid dehydration, but over-drinking before and during exercise have a risk of water intoxication (hyponatraemia). Water is a good option before and during exercise but at a high intensity exercise for longer than one hour, there is benefit further from a sports drink.  They offer an advantage over plain water, to improve performance. This paper’s objectives are to analyze the science behind the formulation of sports drinks and as an information to consider the timing, condition, the amount and the types of fluid intake by athlete: before, during and after exercise. This information is expected to be beneficial for athletes to improve their performance.   Keywords: sports drinks, hyponatraemia, athlete’s performance, dehydration